Guideline-concordant lung cancer care and associated health outcomes among elderly patients in the United States - Nadpara, Pramit A. (J Geriatr Oncol, 2015)
OBJECTIVES: In the United States (US), the elderly carry a disproportionate burden of lung cancer. Although evidence-based guidelines for lung cancer care have been published, lack of high quality care still remains a concern among the elderly. This study comprehensively evaluates the variations in guideline-concordant lung cancer care among elderly in the US. MATERIALS AND METHODS: Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database (2002–2007), we identified elderly patients (aged ≥65 years) with lung cancer (n = 42,323) and categorized them by receipt of guideline-concordant care, using evidence-based guidelines from the American College of Chest Physicians. A hierarchical generalized logistic model was constructed to identify variables associated with receipt of guideline-concordant care. Kaplan–Meier analysis and Log Rank test were used for estimation and comparison of the three-year survival. Multivariate Cox proportional hazards model was constructed to estimate lung cancer mortality risk associated with receipt of guideline-discordant care. RESULTS: Only less than half of all patients (44.7%) received guideline-concordant care in the study population. The likelihood of receiving guideline-concordant care significantly decreased with increasing age, non-white race, higher comorbidity score, and lower income. Three-year median survival time significantly increased (exceeded 487 days) in patients receiving guideline-concordant care. Adjusted lung cancer mortality risk significantly increased by 91% (HR = 1.91, 95% CI: 1.82–2.00) among patients receiving guideline-discordant care. CONCLUSION: This study highlights the critical need to address disparities in receipt of guideline-concordant lung cancer care among elderly. Although lung cancer diagnostic and management services are covered under the Medicare program, underutilization of these services is a concern.